Comunicação social e a Constituição de 1988: programação televisiva e censura - Giorgi, Tania Giandoni Wolkoff (2008)
The present paper brings up the discussion about the need of a judicial control over television programs. Although such control may seem a paradigm in relation to the constitutional prohibition of censorship, it only constitutes an attempt to steer the media, in particular, television broadcasting, into an observation of a loyal obedience to the constitutional principles, as well as to the fundamental rights to the human being and, particularly, to the extremely, presently disrespected notions contained in the Federal Constitution. In this sense, this monography emphasizes human dignity as an enlightening, guiding principle of our juridical system. For such, a brief analysis of concepts related to principles, rules, values and fundamental rights is presented. Likewise, the dispositions related to such concepts, however at times counterposed in our system, are also discussed. At last, the caring that here suggestedly ought to belong to jurisdiction in the composition of conflicts resulted from the disrespect of constitutional rights and principles is considered sinequanon in the composition of television discoursive practices